Normative data on wrist function - Klum, Matthias Peter; Wolf, Maya Barbara; Hahn, Peter; Leclère, Franck Marie Patrick; Bruckner, Thomas; Unglaub, Frank (The journal of hand surgery. [American volume], 2012)
Purpose In clinical day-to-day life, grip strength, key pinch, and range of motion (ROM) serve to objectively evaluate treatment outcomes on wrist interventions. The goals of this study were to generate normative values of wrist function including the parameters of grip strength, key pinch, wrist ROM, and Disabilities of the Arm, Shoulder, and Hand (DASH) scores in a healthy, working population, and to investigate the influence of age, sex, body weight and height, handedness, and work strain.Methods We clinically examined 750 volunteer working subjects (363 women and 387 men, all white). We divided subjects into 2 groups depending on whether their labor involved high or low manual strain. We recorded participants' height, weight, grip strength, pinch strength, and wrist ROM. Each participant filled out a DASH questionnaire.Results Grip strength and pinch strength showed a maximum at between 30 and 49 years of age. In men, body mass index, body height, and weight all correlated with grip strength and pinch grip. Whereas women exhibited greater grip strength on the right side, men showed nonsignificant greater grip strength on the left side. Wrist ROM was greatest for ages ranging between 18 and 29 years. The average DASH value for all male subjects was significantly less than that of female subjects. In a healthy working population, the DASH score increased yearly by an average of 0.2 points in men and 0.3 points in women.Conclusions This study showed that in a healthy working population, people 30 to 49 years of age had the highest grip strength and pinch strength. Age positively correlated with the DASH score and inversely related to wrist ROM. Persons employed in jobs with high manual strain presented with lower wrist ROM and higher DASH scores.Clinical relevance These data help to objectively evaluate wrist function and the effectiveness of therapeutic interventions.
Gesehen am 29.10.2018